1985
DOI: 10.1128/jcm.21.3.442-444.1985
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility and characterization of outer membrane proteins of Haemophilus ducreyi isolated in Thailand

Abstract: One hundred strains of Haemophilus ducreyi isolated in Thailand from patients with chancroid were tested by the agar dilution method against 10 antimicrobial agents and typed by outer membrane protein pattern by using sodium dodecyl sulfate gel electrophoresis. All strains produced beta-lactamase and were resistant to tetracycline, kanamycin, and sulfonamides. Most had a decreased susceptibility to trimethoprim (MIC for 50% of the strains [MIC50], 0.5 ,ig/ml) and chloramphenicol (MIC50, 8 ,ug/ml). Strains were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 22 publications
2
11
1
Order By: Relevance
“…2) have shown that the outer membrane of H. ducreyi appears morphologically similar to those of other gram-negative bacteria (82). The outer membrane protein profile is also typical of gram-negative bacteria, with one to several proteins predominating (1,115,145,164). Typical outer membrane protein profiles for H. ducreyi are shown in Fig.…”
Section: Outer Membrane Proteins and Lpsmentioning
confidence: 91%
See 3 more Smart Citations
“…2) have shown that the outer membrane of H. ducreyi appears morphologically similar to those of other gram-negative bacteria (82). The outer membrane protein profile is also typical of gram-negative bacteria, with one to several proteins predominating (1,115,145,164). Typical outer membrane protein profiles for H. ducreyi are shown in Fig.…”
Section: Outer Membrane Proteins and Lpsmentioning
confidence: 91%
“…Most of the published studies have used the agar dilution method (18,21,51,53,61,75,123,151,155,164,165) to determine the antimicrobial susceptibility of H. ducreyi. However, disk diffusion (27,53) and broth microdilution (84) techniques have also been used.…”
Section: Susceptibility Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been a renewed interest in chancroid since it was shown to be a risk factor for the transmission and acquisition of human immunodeficiency virus (1,13). Until recently, the typing of H. ducreyi strains relied on phenotypic characteristics, viz., outer membrane protein profiles (5,11), lectin typing (4), immunotyping (8), and enzyme profiles (12). In view of the homogeneity of H. ducreyi strains, these techniques are of limited use (3).…”
mentioning
confidence: 99%